α-glucosidase Inhibitory Activity of Probiotic Isolate LBSU9 Isolated from Traditional Food “Trites”: a Preliminary Study - Fachrial, Edy; Ismawati, Ismawati; Nugroho, Titania T; Saryono, Saryono (International Journal of Basic and Applied Science, 2024)
As the prevalence of type 2 diabetes mellitus continues to increase over the years, research into antidiabetic drugs needs to continue. Probiotics are non-pathogenic microorganisms that have potential as α-glucosidase inhibitors. This study aimed to characterize and determine the α-glucosidase inhibitor activity of LBSU9 isolate, a probiotic isolated from "trites," a traditional food of North Sumatra. The results showed that LBSU9 had bacillus morphology, Gram positive, negative catalase test, TSIA (Triple Sugar Iron Agar) A/A test and non-hemolysis. LBSU9 had good tolerance to simulated gastric acid and bile salts, with growth percentages of 66.54% and 64.74%. LBSU9 also has potent antimicrobial activity against S.aureus and E.coli, with 20 mm and 17 mm inhibition zones, respectively. The alpha-glucosidase inhibitor activity of LBSU9 was 98.4% greater than that of acarbose, which was 97%. Based on the results of this study, it is concluded that LBSU9 isolate has the potential to be a complementary therapy to prevent or treat type 2 diabetes mellitus